A NOTE ON THE CONVENTIONAL OUTLIER DETECTION TEST PROCEDURES - GUO, JIANFENG (Boletim de Ciências Geodésicas, 2015)
Under the assumption of that the variance-covariance matrix is fully populated, Baarda’s w-test is turn out to be completely different from the standardized least-squares residual. Unfortunately, this is not generally recognized. In the limiting case of only one degree of freedom, all the three types of test statistics, including Gaussian normal test, Student’s t-test and Pope’s Tau-test, will be invalid for identification of outliers: (1) all the squares of the Gaussian normal test statistic coincide with the goodness-of-fit (global) test statistic, even for correlated observations. Hence, the failure of the global test implies that all the observations will be flagged as outliers, and thus the Gaussian normal test is inconclusive for localization of outliers; (2) the absolute values of the Tau-test statistic are all exactly equal to one, no matter whether the observations are contaminated. Therefore, the Tau-test cannot work for outlier detection in this situation; and (3) Student’s t-test statistics are undefined.